The synergetic effect of initial accounting courses, students performance and professional guidance on accounting career - Grace Akinyi Musa (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
Accounting career has received criticisms right from the University students, Accounting Professional Bodies and the Business World at large. Organizations both public and private sectors have all pointed figures at the poor quality of accounting graduates which Universities are producing. The main objective of this study was to assess the synergetic effect of Initial Accounting Courses, Students Performance and Professional Guidance on Accounting Career. The rationale was that students who performed well in the Initial Accounting courses were expected to excel in the other advanced accounting courses, given the chronological nature of accounting courses. Students were also expected to transfer the same knowledge to the accounting practice in the business world. This would be possible due to students’ relatively higher understanding and appreciation of accounting. It was also expected that Professional Guidance specific to the Accounting Career gave students adequate insights into the discipline that heightened the probability of their choosing Accounting Career. A conceptual framework was used to explain the key factors studied that indicated the interactive relationships amongst them. Four Theories were used including; Wearing Two Hats Theory, Social Learning Theory, Theory of Consumer Behaviour and Theory of Reasoned Action. The population of the study were the Bachelors of Commerce students from 29 Kenyan Universities. The sample comprised of the selected Bachelors of Commerce students from the selected twelve Kenyan Universities. The study adopted a cross sectional research design with a mixture of purposive and stratified random sampling techniques. A pilot study was conducted to test the validity and reliability of the study instruments. A researcher designed questionnaire was used to collect data from sampled students. Logistic regression model was used to test the null hypothesis which was rejected at 5% level of significance. The findings revealed a positive significant synergetic effect of The First Course in Accounting, Students Performance and Professional Guidance on Accounting Career. The study concluded that the synergetic effect of the three variables were greater than the sum of the individual variables. The study’s contribution to knowledge is that the survival of Accounting Career should be pegged on the synergetic effect of the First Course in Accounting, Students Performance and Professional Guidance. Unless this is adopted, Accounting Career’s survival will still be at a risk and therefore remain unresolved.